Innovation outlook : renewable mini-grids (International Renewable Energy Agency, 2016)
IRENA's Renewable Energy Innovation Outlook series analyses emerging trends in renewable energy technologies and examines ways to increase the competitiveness of renewable energy technologies. Each Innovation Outlook identifies technology-, industry- and policy-related challenges to be overcome and assesses the potential breakthroughs and research needed to scale-up the deployment of renewable-based solutions. Renewable mini-grids, offshore wind technologies, advanced liquid biofuels, and ocean energy technologies open the series. This book examines ground-breaking innovations that can help to unlock future power supply for unserved areas and communities through the rapid roll-out of mini-grids based on solar, wind or other renewable sources. Continued research and development (R&D) and innovation are needed to make renewable mini-grids less costly, more environmentally friendly, more reliable and easier to install. The Summary for Policy Makers outlines options to move the technology forward.